The task of ethics education in the context of inclusion. - Shemyhon, N. (Problems of Engineer-Pedagogical Education, 2023)
In Ukraine, significant changes have been taking place in the field of inclusive education, which raises many issues regarding the adaptation of students with special needs to the modern educational space of a general education institution, respectively, the number of complex issues in educational practice that require ethical solutions is increasing. The purpose of this study is to develop the content of ethical education in conditions of inclusion, which will contribute to the increased incorporation of the ethical component in domestic pedagogical education. To determine the content of ethical education, the study uses an axiological approach that allows us to reveal the essence, structure and content of the ethical value orientations of the teaching profession in the field of inclusion. The substantive and procedural aspects of the formation of ethical values of pedagogical activity have been identified in the problem of ethical education of the future teacher. The substantive component of ethical education is implemented through the selection of moral values that serve as a guide for educational activities in the field of inclusion and their incorporation into ethical education. The procedural component is related to informing about the ethical values of the inclusive field and developing complex professional skills necessary to solve educational issues based on certain ethical parameters. We propose to provide the procedural component of ethical education by giving theoretical knowledge on the categories and ethical values of professional and pedagogical activity, which are included in the theoretical course as leading ideas, and which are the core of the value system of pedagogical science. In order to solve the issue of the development of competences of the activity based on certain ethical norms and rules, we recommend the use of methods involving the problematization of the content of training. This makes it possible to offer students problematic issues which contain ambiguity, multifaceted solutions and, respectively, the need to demonstrate the ability to act within the ethical framework of the profession. These are methods of discussing specific situations, role-playing games and dialogue technologies. Thus, the paper describes the axiological approach as a fundamental one for ethical education, and outlines the substantive and procedural aspects of ethical education in the field of inclusion.